Identifikasi Staphylococcus Aureus pada Fermentasi Ikan Pedo Menggunakan Teknik Pewarnaan Gram - Afifatur Rizqiah; Ardi Mustakim (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study aims to identify the presence of Staphylococcus aureus in fermented pedo fish (Decapterus spp.) products using the Gram staining technique. The Gram staining technique is a simple but effective method to distinguish Gram-positive and Gram-negative bacteria based on differences in their cell wall structure. Samples were taken from traditional fermented pedo fish and analyzed in a microbiology laboratory. The results showed the presence of Gram-positive coccus-shaped bacteria that clustered like grapes, in accordance with the morphological characteristics of S. aureus. This identification can be used as an initial step in evaluating the microbiological quality of fermented products.